DEVELOPMENT OF CATHOLIC LITERATURE AND PRESS IN WESTERN UKRAINE (GENESIS, TENDENCIES) - Grom'yak, l. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Genesis and progress trends of catholic literature and press in Western Ukraine is explored in the article. The "organic" of such creation is led to in the west Ukrainian literary-journalistic environment.